Toxicological And Immunological Effects Of Diazinon On The Great Sturgeon (Huso Huso) Of Northern Iran - Khoshbavar Rostam, Hossein Ali (2008)

(untitled)
Great sturgeon (Huso huso) is one of the highly valuable commercial fish species and the major economic resources of Northern Iran. Currently limited data are available on the immunophysiological responses of this valuable species. Unfortunately, within the last decade the average annual sturgeon harvest including great sturgeon from the South Caspian Sea has drastically reduced due to increase pollution problem. Diazinon is one of the most important organophosphorus pesticide groups commonly used in Iranian agriculture, including northern Iran in which both are the natural habitat and aquaculture sites of great sturgeon. In addition also, previous studies had shown that motile Aeromonas septicemia disease is one of the main factors in high mortality outbreaks in the sturgeon farming, particularly whenever the fish immune system is suppressed by some toxicants. Thus, the main objectives of this study were: (i) purification and characterization of great sturgeon immunoglobulin (IgM); (ii) determination of 96-hour LC50 diazinon in great sturgeon; (iii) assessment of some immunophysiological variables of fish following exposure to diazinon; and (iv) assessment of some immunoresponses of fish following treatment with some immunostimulators i.e. glucan and Aeromonas hydrophila antigen. In the immune response assessment, the IgM purified by affinity chromatography under non-reduced condition was found to be 870 kDa, as estimated by SDS-PAGE, while the MWt of the heavy and light chains under reduced condition were estimated at 77-84 and 28-30 kDa, respectively. In the diazinon toxicity study, the LC50 value at 96-hour in fish weighing ca. 14 g under static water quality condition at 22°C was calculated as at 5.63 mg/L. Examination of haematological indices and tissue lysozyme of kidney, liver and spleen showed that exposure to diazinon at sublethal concentration of 1.5 mg/mL as long-term bath caused an effect similar to anaemia. Also, there were significant and insignificant changes in some blood parameters including immunocompetent cell populations, AST, ALP, ALT and LDH enzymes as well as chemiluminescence response of leucocytes at different days post-exposure to diazinon. An almost similar finding was observed when the glucan-injected fish (0.3 mg/kg bwt.) and fish immunized intraperitoneally with a single dose of formalin-killed A.hydrophila (5x107 cells/fish) were exposed to long-term, sublethal concentration of diazinon. However, some of these immunophysiological responses including respiratory burst, immunocompetent cell counts and lysozyme content were enhanced in both glucan-injected fish and immunized fish without diazinon bath. Also, the microagglutination antibody titer in immunized fish was higher than unimmunized fish.In light microscope examinations there were congestion, haemorrhages, focal and generalized necrosis, cellular infiltration, hyperplasia and lamellae fusion as major histopathological changes in the tissues of liver, kidney, spleen and gills of the fish exposed to sublethal dose of diazinon. Also, there were an increase in droplet materials blocking of club cell surfaces in nostrils and barbels tissues; a reduction in excretion of amorphous proteinaceous materials, increase in vesicle numbers and blockage of nostrils epithelial cell surfaces in diazinon exposed fish under scanning electron microscope examination. In conclusion, short and long-term exposure of great sturgeon to diazinon at acute and chronic concentrations changes the basic blood cells constituents causing leucopenia, lymphopenia, neutrophila, erythropenia, hyperglycemia,hypoproteinemia and decreased in both specific antibody production and leucocytes respiratory burst. Thus, avoiding the exposure of endangered juvenile fish to this pollutant is highly recommended. Key words: great sturgeon, Huso huso, diazinon, glucan, A. hydrophila, lysozyme, chemiluminescence response, antibody, immunocompent cells, immunoglobulin, LC50 96-hour.